2016
DOI: 10.1111/cob.12133
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in interdisciplinary weight management in primary care: lessons learned from the 5As Team study

Abstract: SummaryIncreasingly, research is directed at advancing methods to address obesity management in primary care. In this paper we describe the role of interdisciplinary collaboration, or lack thereof, in patient weight management within 12 teams in a large primary care network in Alberta, Canada. Qualitative data for the present analysis were derived from the 5As Team (5AsT) trial, a mixed‐method randomized control trial of a 6‐month participatory, team‐based educational intervention aimed at improving the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
1
29
0
4
Order By: Relevance
“…35,36,37 Most notably, we found ISF's consideration of general team capacity and its impact on an individual's capacity building extremely important. 36,37 Our results illuminate the pathways between knowledge transformation, practice support, and practice delivery (Figure 2). They exemplify pragmatic strategies for achieving sustainable practice change.…”
Section: Resultsmentioning
confidence: 90%
“…35,36,37 Most notably, we found ISF's consideration of general team capacity and its impact on an individual's capacity building extremely important. 36,37 Our results illuminate the pathways between knowledge transformation, practice support, and practice delivery (Figure 2). They exemplify pragmatic strategies for achieving sustainable practice change.…”
Section: Resultsmentioning
confidence: 90%
“…Primary interviews and field notes were revisited to categorize each intervention participant by individual and contextual factors affecting their ability to conduct weight management visits. Factors corresponded to themes identified in our prior qualitative analysis: 24…”
Section: Qualitative and Mixed-methods Analysismentioning
confidence: 86%
“…A priori, we conducted and reported on a detailed qualitative evaluation to understand the facilitators and barriers affecting the primary outcome measure. 23,24 Here we report the convergent mixed-methods analysis that assesses the extent to which these barriers and facilitators affected the uptake of the intervention by the nurses and their impact on the quantity of obesity visits.…”
Section: Qualitative and Mixed-methods Analysismentioning
confidence: 99%
“…18 Sensitive topics discussed during intervention sessions indicated that this was a safe space for participants to speak candidly about interprofessional teamwork. The data were roughly evenly split between positive and negative work environments.…”
Section: Provider-provider Impactsmentioning
confidence: 99%